2022
DOI: 10.1177/09579265221088132
|View full text |Cite
|
Sign up to set email alerts
|

‘Wrap our arms around them here in Ireland’: Social media campaigns in the Irish abortion referendum

Abstract: The 8th Amendment to the Irish Constitution, which codified a near-absolute ban on abortion in Ireland, was ratified in 1983 and removed after a high profile campaign to ‘Repeal the 8th’ in 2018. This article analyses the language of the pro-choice group Together for Yes and the anti-choice groups Love Both and Pro-Life Ireland that campaigned to ‘Save the 8th’. We combine an application of the Appraisal framework with an account of conceptual metaphor in a Critical Discourse Analysis of the language of both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The anti-abortion campaign ("No") focused on the idea that the proposed changes would result in "extreme abortion on demand." It also touched on nativist tendencies and suggested that the new system would be "too British" (Statham & Ringrow, 2022). However, on social media, it refrained from the use of graphic images of foetuses that did appear in some campaign literature.…”
Section: Referendum To Repeal the Constitutional Prohibition On Abortionmentioning
confidence: 99%
“…The anti-abortion campaign ("No") focused on the idea that the proposed changes would result in "extreme abortion on demand." It also touched on nativist tendencies and suggested that the new system would be "too British" (Statham & Ringrow, 2022). However, on social media, it refrained from the use of graphic images of foetuses that did appear in some campaign literature.…”
Section: Referendum To Repeal the Constitutional Prohibition On Abortionmentioning
confidence: 99%